Pernikahan di Bawah Umur Akibat Hamil di Luar Nikah dan Dampak Psikologis Pada Anak di Desa Makrampai Kalimantan Barat - Asman Asman (AL-ISTINBATH : Jurnal Hukum Islam, 2019)
This article aims to learn more about marriage in an aged wawah because of an extramarital pregnancy and the psychological impact on children in the village of Makrampai West Kalimantan. This study uses a qualitative method with a phenomenological approach, namely observations in the field, the authors want to describe how the attention of the people of Makrampai Village in Tebas Subdistrict to underage marriages due to pregnancy out of wedlock itself. From the results of this study it was found that underage marriages in Makrampai Village came from a background of lack of parental attention to their biological children so that their children fell into promiscuity which cannot be changed so that the future of children is damaged and the educational background of parents is also very influential towards the education of children at home. Underage marriage has many impacts on the perpetrator, including depression, anxiety, fear and stress which are the effects of underage marriage in Makrampai Village, Tebas District, Sambas Regency.